Frailty profile in Brazilian older adults: ELSI-Brazil - Juliana Mara Andrade; Yeda Aparecida de Oliveira Duarte; Luciana Correia Alves; Flávia Cristina Drumond Andrade; Paulo Roberto Borges de Souza Junior; Maria Fernanda Lima-Costa; Fabíola Bof de Andrade (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To estimate the prevalence of frailty and to evaluate the associated factors in the non-institutionalized Brazilian population aged 50 years or older. METHODS The analyses were conducted in 8,556 participants of the baseline survey of the Longitudinal Study of Health of the Brazilian Elderly (ELSI-Brazil) conducted in 2015 and 2016. Frailty was defined based on five characteristics: weight loss, weakness, slowness, exhaustion and low level of physical activity. Participants with three or more characteristics were classified as frail. A Poisson regression model was used to examine the association between frailty and sociodemographic and health factors. RESULTS The prevalence of frailty was 9.0% (95%CI 8.0-10.1) among participants aged 50 years or over. Among the older adults aged 60 or over, the prevalence was 13.5% (95%CI 11.9-15.3) and 16.2% (95%CI 14.3-18.3) among those 65 aged years or over. Factors associated with higher prevalence of frailty were low schooling, residence without a partner, health conditions (poor self-rated health and two or more chronic diseases) and limitation to perform basic activities of daily living. CONCLUSIONS The prevalence of frailty among Brazilians aged 65 years or older is similar to their European counterparts. Poor health conditions, functional limitation and low schooling emerge as the factors most strongly associated with the frailty in this population.